Integration of Project Based Learning and Virtual Reality Tour in Descriptive Text Writing Instruction at Junior High School - Ratna Friyandini; Reni Nur Eriyani; Edi Puryanto (Journal of Educational Sciences, 2026)
Writing descriptive text is challenging for junior high school students because they struggle to generate ideas, organize detailed descriptions, and engage in authentic observation. Instruction is also often teacher-centered and rarely uses interactive digital media. This study developed a Project Based Learning–Virtual Reality Tour (PjBL–VRT) model for descriptive text writing using Research and Development (R&D) with the ADDIE model. Needs analysis involved 214 students and seven teachers from eight junior high schools in DKI Jakarta. Three experts validated the model, which was then trialed with Grade VII students at SMP Negeri 59 Jakarta. Validation produced Aiken indices of 0.80–1.00, indicating very high validity. Practicality reached 95.2% for teachers and 93.98% for students. Effectiveness testing showed significant improvement (p < 0.001), with a very large effect size (Cohen’s d = 1.92) and moderate N-Gain (0.60). Thus, PjBL–VRT is valid, practical, and effective for improving descriptive writing skills and supporting 21st-century competencies.